Antioxidant Properties, Texture and Sensory Quality of Sliced Bread Enriched with Leaf Powder from Mango ( Mangifera indica ) - Mónica Pirca-Palomino; Yvette I. Malange; Fernando Ramos-Escudero; Ana María Muñoz; Keidy Cancino-Chávez (Polish Journal of Food and Nutrition Sciences)
Mango leaf ( Mangifera indica L.) is used in traditional medicine and more recently in food applications due to its bioactive compounds that promote healthy effects. The objectives of the present study were to develop a sliced bread (SB) enriched with leaf powder from three mango varieties (Kent, Criollo and Edward) and evaluate the total phenolic content, total flavonoid content and antioxidant capacity. The effect of mango leaf powder on the sensory, textural and chromatic parameters of SB was also assessed. The results showed that bread enriched with mango leaf powder (replacing 2%, 6% and 10% of wheat flour in a bread recipe) compared to control SB had a higher total phenolic content (1.16 to 4.03 mg GAE/g) and antioxidant capacity in the DPPH assay (0.15 to 0.76 µmol TE/g) and in the ferric ion-reducing antioxidant power (FRAP) assay (2.33 to 5.36 µmol FeSO 4 /g). Values of chromatic parameters such as lightness ( L *) decreased from 59.10 to 40.71, when the mango leaf powder percentage in bread increased due to the presence of pigments such as chlorophylls (0.54 to 0.69 mg/g) and carotenoids (2.04 to 2.48 mg/g). Among enriched breads, SBs with 2% mango leaf powder obtained the highest sensory panel scores in terms of color, flavor and odor. The enriched breads were characterized by lower hardness, chewiness and gumminess compared to the control bread. In conclusion, it can be stated that sliced bread enriched with mango leaf powder can be an excellent potential resource of bioactive compounds.